2014
DOI: 10.1099/mic.0.079335-0
|View full text |Cite
|
Sign up to set email alerts
|

Genetic structure and biological properties of the first ancient multiresistance plasmid pKLH80 isolated from a permafrost bacterium

Abstract: A novel multidrug-resistance plasmid, pKLH80, previously isolated from Psychrobacter maritimus MR29-12 found in ancient permafrost, was completely sequenced and analysed. In our previous studies, we focused on the pKLH80 plasmid region containing streptomycin and tetracycline resistance genes, and their mobilization with an upstream-located ISPpy1 insertion sequence (IS) element. Here, we present the complete sequence of pKLH80 and analysis of its backbone genetic structure, including previously unknown featur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 57 publications
2
12
0
1
Order By: Relevance
“…Many of these resistance genes were highly similar to resistance genes found in pathogenic bacteria today, confirming the hypothesis that the antibiotic resistance genes of clinical bacteria originated from environmental bacteria. Taken together, these results support the hypothesis that a reservoir of resistance genes existed in a range of bacteria species prior to the anthropogenic use of antibiotics and contribute to a growing body of evidence demonstrating that antibiotic resistance evolved alongside antibiotic production in the natural environment (Perron et al., ; Petrova et al., ). These results also support the growing body of evidence that nonpathogenic environmental organisms, including those present in the permafrost, are a reservoir of resistance genes that have the potential to be transferred into pathogens, and thus greatly affect the evolution of multidrug‐resistant bacteria in clinical settings (Bhullar et al., ).…”
Section: Introductionsupporting
confidence: 78%
“…Many of these resistance genes were highly similar to resistance genes found in pathogenic bacteria today, confirming the hypothesis that the antibiotic resistance genes of clinical bacteria originated from environmental bacteria. Taken together, these results support the hypothesis that a reservoir of resistance genes existed in a range of bacteria species prior to the anthropogenic use of antibiotics and contribute to a growing body of evidence demonstrating that antibiotic resistance evolved alongside antibiotic production in the natural environment (Perron et al., ; Petrova et al., ). These results also support the growing body of evidence that nonpathogenic environmental organisms, including those present in the permafrost, are a reservoir of resistance genes that have the potential to be transferred into pathogens, and thus greatly affect the evolution of multidrug‐resistant bacteria in clinical settings (Bhullar et al., ).…”
Section: Introductionsupporting
confidence: 78%
“…The ability to confer resistance to various heavy metals or metalloids was demonstrated for pGIAK1, originating from the obligate alkaliphilic and halotolerant Bacillaceae strain JMAK1, pSinA of arsenite oxidizing Sinorhizobium sp. M14 and pSCD of sulfur oxidizer S. denitrificans skB26 (Drewniak et al, 2013; Guo and Mahillon, 2013; Watanabe et al, 2014); while pKLH80 of Psychrobacter maritimus MR29-12, a strain isolated from ancient permafrost, is a novel multidrug-resistant plasmid, carrying genes determining streptomycin, tetracycline and β-lactam resistance (Petrova et al, 2014) (Table 2). …”
Section: Resultsmentioning
confidence: 99%
“…Moreover, it was previously shown that insertion sequence IS Ppy1 of pKLH80 can mobilize for transposition streptomycin ( strAB ), tetracycline ( tetH ) and β-lactam ( bla RTG −6 ) resistance modules (Petrova et al, 2009, 2014). The presence of the resistance modules within transposable elements is of a great importance, since these elements contribute highly in dissemination of the resistance determinants among diverse plasmids co-residing in a single bacterial cell.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The DNA from permafrost can be isolated and queried experimentally for antibiotic resistance genes (among other things). The seminal work of D 'Costa et al (2011) on Beringian permafrost is complemented by studies showing that functional resistance genes can be retrieved from 5000-year-old DNA (Perron et al 2015), and that resistance had mobilized to plasmids and transposons in ancient times (Mindlin et al 2005;Petrova et al 2011Petrova et al , 2014. Modern day microorganisms found in a cave that has been isolated from the surface for four million years have also been shown to harbor functional antibiotic resistance genes (Bhullar et al 2012).…”
Section: Ancient Antibiotic Resistancementioning
confidence: 99%